KUALITAS FISIK DAGING DOMBA YANG DIMARINASI BUAH ANDALIMAN - Wahyu Inul Khomsi (Bajang Institute, 2024)
The research aims to study the physical quality of lamb marinated with andaliman fruit juice. The research used an experimental method with a completely randomized design with a factorial pattern. The first factor was without giving andaliman, the second factor was andaliman 100gr/100 ml of water. The third factor is andaliman 200gr/100 ml water. The third factor is andaliman 300gr/100 ml water. With a soaking period of 30 minutes. The research results showed that it had no real effect on water holding capacity and cooking loss, but had a significant effect on pH